The Persona of the Jurist in Salmond's Jurisprudence: On the Exposition of "What law is ..." - Dorsett, Shaunnagh; McVeigh, Shaun (Victoria University of Wellington Law Review, 2008)
If Sir John Salmond is taken as being an inaugural or founding father of not only a law school, but also of a New Zealand jurisprudence, two questions arise: "What might have been inherited from Salmond's jurisprudence?" And, "How might that inheritance be received today?" This article offers a response to these questions by considering Salmond's jurisprudence in terms of a conduct of life organised around the office and persona of the jurist.